PENGARUH KEMAMPUAN PENALARAN MATEMATIS DAN SELF-EFFICACY TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Rezki Amaliyah AR; Sartika Arifin; Aprianti Aprianti (JURNAL EDUSCIENCE, 2022)
The objective of this study was to determine the effect of mathematical reasoning ability and self- efficacy on mathematics learning outcomes of Class XI MIPA students at SMA Negeri 1 Polewali. This study was ex-post facto research. In addition, samples were Class XI MIPA students of SMA Negeri 1 Polewali, totaling 92 people, selected using simple random sampling. Instruments employed to collect data were (1) the mathematical reasoning ability test, (2) the self-efficacy questionnaire, and (3) the mathematics learning outcomes test. Results showed that: (1) The mathematical reasoning ability of Class XI MIPA students at SMA Negeri 1 Polewali was in the moderate category; (2) The self-efficacy of Class XI MIPA students at SMA Negeri 1 Polewali was in the high category; (3) The mathematics learning outcomes of Class XI MIPA students at SMA Negeri 1 Polewali was in the moderate category; (4) The mathematical reasoning ability had a significant and positive effect on students' mathematics learning outcomes; (5) The self-efficacy had a significant and positive effect on students' mathematics learning outcomes; (6) Mathematical reasoning ability and self-efficacy simultaneously had a significant and positive effect on students' mathematics learning outcomes.